2020
DOI: 10.1021/acsami.0c03750
|View full text |Cite
|
Sign up to set email alerts
|

Co9S8 Nanorods as an Electrocatalyst To Enhance Polysulfide Conversion and Alleviate Passivation in Li–S Batteries under Lean Electrolyte Conditions

Abstract: As a result of the high theoretical energy density of lithium−sulfur (Li−S) batteries, they have been accepted as the nextgeneration energy storage system. Nevertheless, the current performance of Li−S batteries is still unsatisfactory under lean electrolyte conditions. It is because of sluggish deposition of Li 2 S 2 /Li 2 S passivating the sulfur/ electrolyte interface, thus leading to lower sulfur use and bad rate performances of Li−S batteries. Herein, a novel Co 9 S 8 nanorod-based catalytic interlayer pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…These results indicate that the P-CoS 2 /CNTs layer prevents polysulfides from shuttling during the rest. Finally, the high sulfur loading increases the areal capacity of the cathode and compensates for the dead weight of the inactive components in Li–S batteries, ,, and thus, the cell with P-CoS 2 /CNTs@Celgard was also tested under high areal loading conditions . As shown in Figure c, the Li–S batteries with an areal sulfur loading of 2.6 and 4.8 mg cm –2 deliver areal capacities of 2.6 and 4.5 mA h cm –2 after 100 cycles at 0.2 C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the P-CoS 2 /CNTs layer prevents polysulfides from shuttling during the rest. Finally, the high sulfur loading increases the areal capacity of the cathode and compensates for the dead weight of the inactive components in Li–S batteries, ,, and thus, the cell with P-CoS 2 /CNTs@Celgard was also tested under high areal loading conditions . As shown in Figure c, the Li–S batteries with an areal sulfur loading of 2.6 and 4.8 mg cm –2 deliver areal capacities of 2.6 and 4.5 mA h cm –2 after 100 cycles at 0.2 C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, this is not the case in a real cell scenario, where E/S < 4.5 is highly advocated to achieve the high-energydensity goal [11,71,77]. Several approaches have been considered to realize efficient operation of Li-S batteries with a low E/S ratio: (i) Spatially confining sulfur into microstructured carbon materials to avoid the triphasic interface limitation, and electrode optimization to reduce porosity [78][79][80][81][82][83][84]; (ii) heterogeneous or homogeneous mediator to promote liquid-solid conversion and control morphology of solid deposits [85][86][87][88][89][90]; (iii) design of electrolyte with desired solvation properties to find new reaction pathways to break electrolyte-quantity-dependent limitations of sulfur redox reactions [91,92]. Especially, a breakthrough of electrolyte that can be applied under starved conditions would provide a driving force to bring Li-S batteries into reality.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, metal Co and cobalt sulfides (such as CoS 2 , Co 3 S 4 , and Co 9 S 8 ) with high surface free energy and abundant active sites, have been shown high catalytic activity to promote the sulfur conversion process in LSBs. [6,[38][39][40][41][42] For example, Dai and co-workers [43] confirmed that the honeycomb-like Co 9 S 8 tubules had high binding energies which could effectively remit the dissolution and promote the redox reaction kinetics of LiPSs. Qian et al [44] introduced a catalytic interlayer, Co nanoparticles embedded in the skeleton surface, improved the Li 2 S conversion, and enhanced the battery performances.…”
Section: Introductionmentioning
confidence: 99%